Literature Review: Perkembangan dan Kinerja Bank Umum Syariah di Indonesia Tahun 2014-2023 - Juliyanti, Wiwin (Penerbit Goodwood, 2023)
Purpose: This study investigates the development and performance of Islamic commercial banks in Indonesia from 2013 to the present, focusing on the factors that influence growth and the challenges faced by the Islamic banking sector in supporting economic stability and inclusiveness. Methodology/approach: This research uses a literature review method of 30 previous research articles from the Google Scholar and Research Gate sites, which measure the financial performance of Islamic Banks in Indonesia in terms of profitability during the publication period–2013-2023. Results/findings: This research study reveals that several studies on Islamic Banks in Indonesia use various indicators to measure financial performance and bank health, > 60% of researchers use the variable measurement ratios ROA, ROE, BOPO, CAR, FDR and NPF while the rest some use the LDR, RGEC, NIM, CGC, ETA, EFF, NPL and DPK ratios Limitations: The use of research methods in the form of literature that focuses on the analysis of several previous studies conducted by Google Scholar and ResearchGate can reduce the validity and generality of the research results. The literature review does not involve collecting primary data through observation or experimentation; therefore, the information obtained is descriptive and does not allow the identification of causal relationships. Contribution: Through a careful literature review of previous articles, this study succeeded in identifying the main trends, innovations, and challenges faced by the Islamic banking sector in Indonesia.